Mn2+‐Phos‐Tag Polyacrylamide for the Quantification of Protein Phosphorylation Levels. Issue 8 (19th August 2021) - Markandran, Kasturi; Xuan, Jane Vanetta Lee En; Yu, Haiyang; Shun, Lim Meng; Ferenczi, Michael A.
Abstract: This paper provides a guideline for optimizing and utilizing Mn 2+ Phos‐tag gel technology to separate phosphorylated proteins from their unphosphorylated counterparts. It provides key insights into methods for careful sample preparation and experimental directions for determining the appropriate Phos‐tag gel compositions and electrophoresis and western blotting conditions. This protocol has been used to successfully resolve proteins extracted from cardiac and skeletal muscles. The guidelines can be extended for optimizing protocols to resolve proteins from other cells or tissue sources. With this, phosphoproteomics and the elucidation of underlying mechanisms of disease progression can be accelerated. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC.